Variability of the period between germination and heading in spring barley accessions from Dagestan - I. A. Zveinek; R. A. Abdullaev; B. A. Batasheva; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
Background. The genetic variability of the period between the germination and heading phases was analyzed in barley accessions from the Republic of Dagestan planted in the southern area of Dagestan (Derbent) and the Northwest of Russia (Pushkin, St. Petersburg). Testing barley development rates under contrasting climate conditions of Russia makes it possible to assess the paratypic variability and a norm of reaction in the tested accessions in order to identify environmentally adaptable plant forms useful for breeding.Materials and methods. Under spring sowing, 173 spring barley accessions were studied for the duration of the period from germination to heading. To compare the earliness of accessions planted at two sites with different sowing schedules, “the rate by which the germination-to-heading period of an accession exceeded its minimum value across the sample” was used as a criterion for calculations.Results and conclusions. Accession k-15013 was the earliest at both test sites during two years of studying. In Dagestan, accessions k-11439 and k-11475 with a low norm of reaction in 2016 and 2017 were also identified as early. Environmental conditions were found to have a significant effect on the development rate of barley accessions in Derbent and St. Petersburg. Dagestani barleys in the North-west of Russia ripened earlier than in the south of Dagestan during all the years of study. Vernalization temperatures proved to be the main factor affecting maturation schedules of local Dagestani barleys in the area of their distribution. A longer day and the absence of high temperatures in St. Petersburg contributed to the earliness of barley accessions.